2008
DOI: 10.1111/j.1468-1331.2007.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of systemic TNFα in Natalizumab‐treated multiple sclerosis

Abstract: The mRNA expression of eight different cytokines in peripheral blood mononuclear cells in 19 individuals with multiple sclerosis was determined at baseline and after 6 months of open-label treatment with natalizumab. Cellular expression of tumor necrosis factor alpha (TNFalpha) mRNA and number of cells secreting TNFalpha and interferon gamma protein significantly increased over the 6 months. Kurtzke EDSS scores improved because of the resolution of relapses, but not fatigue severity scores. The observed increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
3
17
1
1
Order By: Relevance
“…As NTZ treatment is known to increase the numbers of multiple lymphocyte subsets in peripheral blood [6][8], [22], we would have expected to find an increased frequency of PDCs in the circulation during NTZ treatment [2][4]. We calculated the frequency of PDCs in total live PBMCs and it is possible that the decrease in PDC frequency is reflecting an increase in other lymphocyte subsets during NZT treatment rather than a decrease in PDC numbers per se [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As NTZ treatment is known to increase the numbers of multiple lymphocyte subsets in peripheral blood [6][8], [22], we would have expected to find an increased frequency of PDCs in the circulation during NTZ treatment [2][4]. We calculated the frequency of PDCs in total live PBMCs and it is possible that the decrease in PDC frequency is reflecting an increase in other lymphocyte subsets during NZT treatment rather than a decrease in PDC numbers per se [22].…”
Section: Discussionmentioning
confidence: 99%
“…NTZ is known to inhibit T cell trafficking to the CNS by blocking the interactions between VLA-4 on T cells and VCAM-1 on cerebral endothelial cells, a step that is required for T cell extravasation to the CNS. Previous studies have shown that NTZ treatment in MS is associated with increased frequencies of activated CD4+ T cells producing proinflammatory cytokines such as IFN-γ, TNF, and IL-17 in peripheral blood [2][5]. Such effects of NTZ are, however, not limited to activated CD4+ T cells, but an increase in peripheral blood frequencies of total T cells, B cells, and NK cells has also been demonstrated, while frequencies of monocytes were decreased [6][9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for a direct relationship of fatigue and inflammatory activity also comes from immunological studies that found increased peripheral proinflammatory cytokine levels e. g. TNF-alpha, Interferon-gamma in patients with fatigue [6,11]. Since natalizumab increases peripheral TNF-alpha and Interferon-gamma levels, it is implausible that natalizumab could exhibit a positive effect in this way [28]. But since natalizumab hinders migration of leukocytes into the CNS, any change on the peripheral level of cytokines probably has little reflection on their levels within the CNS.…”
Section: Fatigue and Cns Inflammationmentioning
confidence: 94%
“…Although it is clear that pro-inflammatory cytokines are a key element of the MS disease process [31], direct evidence of the role of cytokines in fatigue in MS is sparse and inconsistent. An increased level of TNF-alpha expression was found in fatigued compared with non-fatigued subjects [34,35], but following therapy, changes in TNF-alpha expression were not associated with changes in fatigue [36]. The small sample sizes in these few studies make their negative results uninformative, thus leaving the question largely unanswered.…”
Section: Immunological Factorsmentioning
confidence: 95%